2009
DOI: 10.2322/tjsass.52.89
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Computational Studies of Low-Speed Aerodynamic Performance and Flow Characteristics around a Supersonic Biplane

Abstract: One of the most critical technical issues with regard to supersonic commercial transportation is the sonic boom that occurs during supersonic cruising flight, which causes impulsive noise on the ground. The ''supersonic biplane theory'' has been proposed to reduce the sonic boom. Shock wave interaction and cancellation between the wings of a supersonic biplane can be realized at a specific design Mach number, but does not work at off-design values. Here, the low-speed aerodynamic performance, as off-design per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…As the supersonic aircraft has to undergo subsonic flight at high angles of attack during takeoff and landing, the problems associated with off design low subsonic flights also become important. In this regard, Kuratani et al [14] have experimentally and numerically studied the stall characteristics of supersonic biplane and suggested that the stall is caused by stall in both the upper and lower airfoils at about 20 • . They also found that at low subsonic speeds the lower airfoil dominates the lift produced and also accounts for major proportion of drag at high angles of attack.…”
Section: Introductionmentioning
confidence: 97%
“…As the supersonic aircraft has to undergo subsonic flight at high angles of attack during takeoff and landing, the problems associated with off design low subsonic flights also become important. In this regard, Kuratani et al [14] have experimentally and numerically studied the stall characteristics of supersonic biplane and suggested that the stall is caused by stall in both the upper and lower airfoils at about 20 • . They also found that at low subsonic speeds the lower airfoil dominates the lift produced and also accounts for major proportion of drag at high angles of attack.…”
Section: Introductionmentioning
confidence: 97%
“…Yamashita et al have suggested various methods to overcome the issues of choking and hysteresis encountered in Busemann biplane configuration by incorporating leading edge and trailing edge flaps [9]. Kurutani et al studied the Busemann biplane's stall characteristics and found that the stalling angle of attack is 20˚ for both the upper and lower element of the biplane [10]. They also found that the lower element of the biplane dominates the lift produced and produces a high amount of drag at low subsonic speed and a high angle of attack.…”
Section: Introductionmentioning
confidence: 99%